PANDANGAN KEPALA KANTOR URUSAN AGAMA (KUA) MELAWI TERHADAP FENOMENA PERNIKAHAN BEDA AGAMA DI KABUPATEN MELAWI - Julianto, Rendi; Hasan, Muhammad; Wibowo, Arif (Al-Usroh, 2023)
The purpose of this study was to find out: 1) To find out the views of the head of the office of religious affairs (kua) melawi on interfaith marriages between Muslim men and non-Muslim women. 2) To find out the views of the head of the office of religious affairs (kua) Melawi on interfaith marriages of non-Muslim men and Muslim women. Primary data source Head of Religious Affairs Office (KUA) Melawi. This study uses interview data collection techniques. Meanwhile, data analysis by reducing the very basic things is then summarized to be presented in the form of a narrative. So that it can be concluded, the data is also checked for validity by triangulating sources. The results showed: 1) The views of the head of the Office of Religious Affairs (KUA) Melawi on interfaith marriages, where Muslim men marry non-Muslim women, namely that there are those who state that it is not permissible based on QS Al-Baqarah 221, Law Number 16 of 2019 Amendments to Law Number 1 of 1974, the Compilation of Islamic Law, and the 2005 MUI Fatwa concerning interfaith marriages. In addition, there are also those who say that marriage is permissible as long as it is with an ahlul Kitab based on QS Al-Maidah 5, and the jurists of 4 schools of law allow interfaith marriages with an ahlul Kitab. 2) The view of the head of the Office of Religious Affairs (KUA) melawi on interfaith marriages for non-Muslim men marrying Muslim women. All heads of KUA Melawi agree that interfaith marriages for Muslim men marrying non-Muslim women are illegal and unlawful based on QS Al-Baqarah 221, QS Al-Mumtahanah 10, Law No. 16 of 2019 Amendments to Law No. 1 of 1974, the Compilation of Islamic Law, and the 2005 MUI Fatwa on interfaith marriages.